In vivo analysis of choroid plexus morphogenesis in zebrafish. - Marta García-Lecea (Public Library of Science (PLoS), 2008)
Background The choroid plexus (ChP), a component of the blood-brain barrier (BBB), produces the cerebrospinal fluid (CSF) and as a result plays a role in (i) protecting and nurturing the brain as well as (ii) in coordinating neuronal migration during neurodevelopment. Until now ChP development was not analyzed in living vertebrates due to technical problems. Methodology/principal findings We have analyzed the formation of the fourth ventricle ChP of zebrafish in the GFP-tagged enhancer trap transgenic line SqET33-E20 (Gateways) by a combination of in vivo imaging, histology and mutant analysis. This process includes the formation of the tela choroidea (TC), the recruitment of cells from rhombic lips and, finally, the coalescence of TC resulting in formation of ChP. In Notch-deficient mib mutants the first phase of this process is affected with premature GFP expression, deficient cell recruitment into TC and abnormal patterning of ChP. In Hedgehog-deficient smu mutants the second phase of the ChP morphogenesis lacks cell recruitment and TC cells undergo apoptosis. Conclusions/significance This study is the first to demonstrate the formation of ChP in vivo revealing a role of Notch and Hedgehog signalling pathways during different developmental phases of this process.